Integration of Risk Thresholds into Enterprise Risk Management (ERM) Implementation in An Energy Company - Willy Januardi; Putu Dana Karningsih; Demi Ramadian (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
All state-owned enterprises are obligated to implement risk management effectively. Risk management implementation can be assessed using the Risk Maturity Index (RMI). The 2024 RMI assessment at one of the state-owned energy subsidiaries indicated that the Company is at the "Developing" stage (score 2.9 out of 5). Critical weaknesses occurred because the company had not conducted a comprehensive risk capacity calculation. Risk capacity constitutes a key component of an organization's risk threshold and serves as the basis for determining risk appetite, risk tolerance, and risk limits. This study aims to identify an appropriate method for calculating the risk threshold value and to apply the selected approach for the year 2026. Risk capacity is calculated based on the Company's financial statements from 2019 to 2024 using a Modified Altman Z-Score approach is proposed to determine the financial distress point as a measure of risk capacity. The resulting risk capacity was estimated at IDR 1.42 trillion and subsequently validated using the Value at Risk (VaR) method. The findings of this study are expected to provide a quantitative basis for the Company in formulating its 2026 risk strategy, while also contributing to the improvement of its RMI score.